Ulinastatin May Significantly Improve Postoperative Cognitive Function of Elderly Patients Undergoing Spinal Surgery by Reducing the Translocation of Lipopolysaccharide and Systemic Inflammation - Zhang, Min; Zhang, Yan-Hua; Fu, Hui-Qun; Zhang, Qing-Ming; Wang, Tian-Long (Frontiers in Pharmacology, 2018)
Abstract Purpose: To investigate the effects of ulinastatin on inflammatory response and early postoperative cognitive function in elderly patients undergoing spinal surgery. Methods: This clinical trial was approved by the Xuanwu Hospital Ethical Committee (Registration number: ChiCTR-IPR-16008931). Sixty elderly patients undergoing elective spinal surgery with ASA status of I–II were randomized into ulinastatin and control groups; total intravenous anesthesia was performed. The elderly patients in ulinastatin group underwent intravenous infusion of ulinastatin 10,000 units/kg following anesthesia induction and before surgical incision, and 5000 units/kg on postoperative days 1 and 2. Cognitive function was determined with Montreal Cognitive Assessment test preoperatively and on postoperative day 7 by a neurologist. Serum lipopolysaccharide (LPS), interleukin-6 (IL-6), C-reactive protein (CRP), and matrix metalloprotease-9 (MMP-9) concentration levels were measured at baseline, the end of surgery, and on postoperative days 1 and 3. Results: All elderly patients completed the study. Ulinastatin infusion significantly reduced the incidence of postoperative cognitive dysfunction in elderly patients undergoing spine surgery (ulinastatin group 16% vs. control group 43%, P< 0.05). The elderly patients in ulinastatin group exhibited lower serum LPS, IL-6, CRP, and MMP-9 concentrations, as well as a shortened peak value duration, compared with those in the control group following surgery (P< 0.05). Conclusion: Systemic inflammation and translocation of LPS were inhibited by the infusion of ulinastatin in elderly patients undergoing spinal surgery. The anti-inflammation intervention with ulinastatin can significantly improve the elderly patients’ postoperative cognitive function. Keywords: Ulinastatin, elderly patients, spine surgery, lipopolysaccharide, systemic inflammation, POCD